2016
DOI: 10.1016/j.cyto.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammatory biomarkers by intravenous methylprednisolone in pediatric ARDS patients: Results from a double-blind, placebo-controlled randomized pilot trial

Abstract: Objective A double-blind, randomized controlled trial showed that low-dose glucocorticoid therapy in pediatric ARDS patients is feasible and may improve both ventilation and oxygenation indices in these patients. However, the molecular mechanisms underlying potential changes in outcomes remain unclear. Based on these clinical findings, this study was designed to examine the effects of intravenous methylprednisolone on circulating inflammatory biomarkers in pediatric ARDS patients. Design Double-blind, placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In adult ARDS, the same MPT protocol was associated with decreases in plasma IL-6 and proadrenomedullin levels and increases in protein C levels, compared to the placebo ( 39 ). As previously reported, MPT decreased IL-6 in pediatric ARDS as well ( 8 ). Considering the biomarker changes in this study, we propose that corticosteroids may attenuate inflammation, promote early recovery from the epithelial injury, and prevent sustained endothelial damage, leading to earlier improvement in pulmonary edema and oxygenation seen as clinical outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In adult ARDS, the same MPT protocol was associated with decreases in plasma IL-6 and proadrenomedullin levels and increases in protein C levels, compared to the placebo ( 39 ). As previously reported, MPT decreased IL-6 in pediatric ARDS as well ( 8 ). Considering the biomarker changes in this study, we propose that corticosteroids may attenuate inflammation, promote early recovery from the epithelial injury, and prevent sustained endothelial damage, leading to earlier improvement in pulmonary edema and oxygenation seen as clinical outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…MPT therapy did not alter ventilator-free days or mortality but appeared to alter oxygenation and ventilation ( 6 ). We also examined different regulatory patterns of pro- and anti-inflammatory plasma cytokines in the MPT and placebo groups to identify several cytokines as potential predictors for alterations in clinical parameters of disease severity ( 8 ). Larger randomized controlled studies are warranted for investigating corticosteroid use in early pediatric ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 is a major anti-inflammatory cytokine, and elevations in plasma and BAL fluid have been associated with the development of ARDS as well as with ARDS mortality in adults ( 80 , 82 , 83 ). It appears that an early rise in IL-10 at the onset of ARDS is followed by normalization of levels over the first 21 days of illness ( 74 ), and this pattern was also seen in children with ARDS, both with and without steroid therapy ( 16 , 20 ). IL-10 is elevated in newborns with RDS ( 22 ), independent of gestational age, and has also been associated with increased development of ARDS and increased mortality among pediatric burn patients with inhalation injury ( 17 ).…”
Section: Biomarker Subgroupsmentioning
confidence: 92%
“…IL-1 and IL-6 levels in BAL fluid were also both found to be elevated in premature babies with RDS and were correlated with the development of chronic lung disease (CLD) ( 56 , 58 , 59 ). As a biomarker of response to therapy, IL-6 was recently found to decrease in response to glucocorticoid (GC) therapy in a randomized trial of GC therapy in children ( 20 ). The relationship of the inflammatory cytokine response to ventilation strategies was also demonstrated in the landmark ARDSNet trial of low-tidal-volume ventilation, where IL-6 and IL-8 levels were observed to decrease in the low-tidal-volume group compared with the controls ( 79 , 80 ).…”
Section: Biomarker Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation